Inuit youth and environmental research: exploring engagement barriers, strategies, and impacts - Sadowsky, Hilary; Brunet, Nicolas D.; Anaviapik, Alex; Kublu, Abraham; Killiktee, Cara; Henri, Dominique A. (FACETS, 2022)
Community leadership in Arctic environmental research is increasingly recognized as one of many pathways to Indigenous self-determination in Nunavut, Canada. While experienced Inuit hunters, trappers, and other recognized environmental knowledge experts are commonly included in research, similar opportunities for Inuit youth to meaningfully engage in environmental research remain limited. Finding ways to increase scientific literacy, particularly among Inuit youth, has been identified as an important step in the continuation of high-quality Arctic environmental research. This paper examines community perspectives on the roles and contributions of Inuit youth in environmental research in Nunavut, barriers that Inuit youth face in becoming meaningfully engaged in field-based environmental research, and strategies for enhancing Inuit youth engagement. Our study was conducted in Pond Inlet, Nunavut, and used interviews, workshops, and observation to gather stories and knowledge from community members about field- and land-based experiential learning pathways. This study found that a complex set of barriers, including a lack of credentials and support systems, among others, may inhibit meaningful Inuit youth engagement in environmental research. Key findings from the study support the view that collaborative land-based research activities can be an effective and meaningful method of enhancing scientific literacy among Inuit youth.